Then and now : language, ethnolinguistic vitality, and the Finns of Lake Worth and Lantana, Florida - Ontermaa, Marie (2019)
This study centers on the adult children of Finnish immigrants to Florida, specifically the Lake Worth and Lantana areas of South Florida, looking retrospectively at their language development in Finnish and English, as well as at their current state of language development and preference. Using informal, semi-structured interviews, the study considers the influence of the local Finnish community’s ethnolinguistic vitality on the transmission, maintenance, and family language policies of these Finns. Cultural identification to Finland remains strong; however, the younger American Finns speak increasingly less Finnish because of lack of necessity in daily life. Factors such as family language policy, the cultural and linguistic identity of a spouse, and internal motivation also contribute to the levels of language maintenance.